2022
DOI: 10.1101/2022.02.14.480335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virological characteristics of SARS-CoV-2 BA.2 variant

Abstract: Soon after the emergence and global spread of a new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron lineage, BA.1 (ref1, 2), another Omicron lineage, BA.2, has initiated outcompeting BA.1. Statistical analysis shows that the effective reproduction number of BA.2 is 1.4-fold higher than that of BA.1. Neutralisation experiments show that the vaccine-induced humoral immunity fails to function against BA.2 like BA.1, and notably, the antigenicity of BA.2 is different from BA.1. Cell culture ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
224
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(250 citation statements)
references
References 52 publications
(187 reference statements)
23
224
1
Order By: Relevance
“…A recent study using in vitro neutralization assays reported that there were differences in the reactivity of several mAbs against these different Omicron sublineages 38 . These observations suggest that BA.2 are antigenically distinct from BA.1 and BA.1.1, which is consistent with the data performed convalescent hamster sera 3 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent study using in vitro neutralization assays reported that there were differences in the reactivity of several mAbs against these different Omicron sublineages 38 . These observations suggest that BA.2 are antigenically distinct from BA.1 and BA.1.1, which is consistent with the data performed convalescent hamster sera 3 .…”
Section: Discussionsupporting
confidence: 92%
“…Our study suggests that the pathogenicity and replicative ability of the BA.2 variant is comparable to that of BA.1 variants in animal models. In contrast, a recent study showed that a recombinant, chimeric SARS-CoV-2 possessing the BA.2 S gene in the background of an ancestral SARS-CoV-2 strain is more pathogenic than a recombinant virus bearing the BA.1 S gene in the same background 3 , suggesting that the differences in the BA.1 and BA.2 S genes are responsible for the difference in pathogenicity between these chimeric viruses; based on these data, the authors concluded that BA.2 is more pathogenic than BA.1. However, in natural isolates, the genomes of BA.1 and BA2 also differ at locations other than the S gene, and these differences could have epistatic or independent effects that offset differences in pathogenic potential of the S gene 43 .…”
Section: Discussionmentioning
confidence: 83%
“…In vaccine-boosted individuals, BA.1, BA.1.1 and BA.2 showed no significant difference in plasma neutralization resistance (Fig. 1a-b), which is concordant with several recent research 4,16 . However, this does not necessarily mean BA.2 displays similar antigenicity with BA.1 and BA.1.1.…”
Section: Mainsupporting
confidence: 92%
“…We investigated whether these variants produce less aberrant 5′ end svRNAs in human cells. Compared with the parental strain, the Omicron variants BA.1 and BA.2 (termed BA.1 and BA.2) replicated less well in Calu-3 cells as reported previously (Yamasoba et al, 2022), with the most drastic difference observed at 33ºC rather than 37ºC (Figure 7A). IFN-b expression was markedly attenuated, although nally achieving a substantial level at 120 hpi at 37ºC but not 33ºC (Figure 7B), whereas IL-6 expression was less reduced in Omicron-infected cells (Figure 7C).…”
Section: Resultssupporting
confidence: 75%